The Impact of Means of Communication on Electoral Behavior and its Relationship to the Political Disparity of the Family (A Field Study of an Audience of the University of Baghdad’s Students) - al-Uqaili, Jihad Kadhim (ALBAHITH ALALAMI, 2013)
Iraq has seen many changes at the social, economic and political levels. This led to cause many shifts in the structure of its society and imposed great challenges reflected in the behavior and awareness of that society in general and youth in particular. Those changes made the Iraqi society undergoing the transformation of value and culture aspects formed a political awareness that caused cultural and political diversity within the family and society. A greater openness to the outside world caused by the communication revolution, as the world has witnessed during the past two decades, has helped in making that change. Iraq had its share of media and political openness, which were included after the US occupation in 2003. As a result, those changes left a significant impact on the electoral behavior of the family in the process of electoral participation. The research focused on studying the impact of communication on the dissemination of political awareness and the promotion of political disparity in the family and its relationship to the electoral behavior of students as a result of the exposure to various political programs and topics through the programs they prefer to follow up as a received information for both genders. The study goes further to study the match and the different visions among family members on participating in the political process; to examine the freedom of opinion between students and their families, and to discuss topics or political programs handled by means of different communication. My sample was drawn from the students of the University of Baghdad of Fourth-Year students of both branches: humanitarian and scientific. The researcher concluded that the means of communication is of great importance in spreading political awareness through various programs and topics that included the Iraqi political case, and in enriching the means of communication with the abundant information for the family members. The means of communication have helped to create different visions and ideas among members of the same family and to create a state of political disparity among family members due to dialogues and discussions between students and their families. The presence of the good educational level of the family has helped in stimulating, influencing and imparting a culture of dialogue; and added space of freedom of opinion and other’s opinions. The existence of the intersection, however, facilitated the choices of students and their families in voting. This considered as another indicator of the state of disparity and disagreement in the selection of political blocs, which was done in accordance with the bases and criteria preferred by students, including competence and scientific experience and then political experience.